2020
DOI: 10.1136/jnnp-2020-323226
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CASPR2 clinical phenotypes correlate with HLA and immunological features

Abstract: ObjectiveAntibodies against contactin-associated protein-like 2 (CASPR2-Abs) have been described in acquired neuromyotonia, limbic encephalitis (LE) and Morvan syndrome (MoS). However, it is unknown whether these constitute one sole spectrum of diseases with the same immunopathogenesis or three distinct entities with different mechanisms.MethodsA cluster analysis of neurological symptoms was performed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 26 publications
3
48
1
Order By: Relevance
“…In addition, another study, besides replicating the above-mentioned HLA association with LGI1-mediated encephalitis, described an additional association between the HLA-DRB1*11:01∼DQA1*05:01∼DQB1*03:01 haplotype and anti-contactin-associated protein-2 (CASPR2) encephalitis ( Binks et al, 2018 ). Further, it has been recently suggested that the genetics of the HLA cluster may help to stratify anti-CASPR2-related clinical subtypes ( Muñiz-Castrillo et al, 2020 , Binks and Irani, 2020 ). Whether and how the HLA system is involved in the autoimmune encephalitis/psychosis remains an open question and will be an important avenue for future research, especially given the heightened levels of autoantibodies against the NMDA-R in 20% of patients diagnosed with schizophrenia (Jezequel et al, 2017).…”
Section: Hla Alleles and “Autoimmune Psychosis”mentioning
confidence: 99%
“…In addition, another study, besides replicating the above-mentioned HLA association with LGI1-mediated encephalitis, described an additional association between the HLA-DRB1*11:01∼DQA1*05:01∼DQB1*03:01 haplotype and anti-contactin-associated protein-2 (CASPR2) encephalitis ( Binks et al, 2018 ). Further, it has been recently suggested that the genetics of the HLA cluster may help to stratify anti-CASPR2-related clinical subtypes ( Muñiz-Castrillo et al, 2020 , Binks and Irani, 2020 ). Whether and how the HLA system is involved in the autoimmune encephalitis/psychosis remains an open question and will be an important avenue for future research, especially given the heightened levels of autoantibodies against the NMDA-R in 20% of patients diagnosed with schizophrenia (Jezequel et al, 2017).…”
Section: Hla Alleles and “Autoimmune Psychosis”mentioning
confidence: 99%
“…This heterogeneous nature in anti-Caspr2 Ab-associated syndrome was subsequently confirmed by Muñiz-Castrillo and colleagues [ 121 ]. In 2020, using cluster analysis on 56 patients, the authors clarified that the anti-Casp2 Ab-associated syndrome was separated into two groups without overlapping, a limbic-predominant group and peripheral nerve hyperexcitability-predominant (PNH) group [ 121 ]. The former group (52%) developed limbic symptoms alone (LE/-) or with extra-limbic symptoms (LE/+).…”
Section: Clinical Autoimmune Background and Pathophysiological Actmentioning
confidence: 59%
“…In the paper by Muñiz-Castrillo, the authors explain the complexity underlying the CASPR2-antibody diseases using a data-driven approach to phenotyping, in parallel with immunological and genetic markers integral to disease pathogenesis. 5 …”
Section: Muñiz-castrillo Aims Towards Precision Medicine In Caspr2-anmentioning
confidence: 99%
“…In the paper by Muñiz-Castrillo, the authors explain the complexity underlying the CASPR2antibody diseases using a data-driven approach to phenotyping, in parallel with immunological and genetic markers integral to disease pathogenesis. 5 By cluster analysis, 56 patients with CASPR2-antibodies were divided into four groups: (i) a relatively isolated limbic encephalitis (LE) ('LE/-'; n=18), (ii) LE 'plus' non-limbic symptoms, including cerebellar ataxia, movement disorders, dysautonomia and weight loss ('LE/+'; n=11), (iii) a group with severe peripheral nerve hyperexcitability (PNH), plus dysautonomia, dyssomnia and malignant thymoma, but without limbic featuresclosely resembling contemporary descriptions of Morvan's syndrome ('PNH/+'; n=16) 2 and (iv) a less severe form of PNH with only few associated central nervous system (CNS) features ('PNH/-'; n=11). These phenotypes explained some of the variance observed across paraclinical findings, such as inflammation on MRI/cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%